Education on the Practical Use of Herbs in Anemia Prevention for Female Eleventh Graders at SMK Negeri 3 Samarinda: Edukasi Pemanfaatan Herbal dalam Pencegahan Anemia pada Siswi Kelas XI SMK Negeri 3 Samarinda - Akhsa Anggina Silaban; Dina Salsabila; Oktaviani Zahra Zattira; Islamudin Ahmad (ANDIL Mulawarman Journal of Community Engagement, 2026)
Anemia remains a significant health problem among adolescent girls, including in East Kalimantan, with a prevalence of 43.2%. Low adherence to iron supplementation (iron tablets) and limited understanding of dietary iron sources pose challenges to prevention efforts. This study employed a one-group pretest–posttest design involving 25 eleventh-grade students of SMK Negeri 3 Samarinda. The intervention consisted of interactive education on anemia prevention and herbal utilization through the distribution of leaflets, posters, discussion sessions, and iron tablet supplementation, followed by effectiveness evaluation using pre-test, post-test, and questionnaires. The results showed an improvement in knowledge, indicated by an increase in the number of students with correct answers from 20 in the pre-test to 23 in the post-test, with the greatest improvement observed in understanding anemia symptoms and the benefits of iron supplementation. Adherence to iron tablet consumption was also high, with 96% of students reporting consumption at home. Interactive education was effective in improving students’ knowledge and awareness in preventing anemia. The use of commonly available herbal resources can serve as a complementary strategy for anemia prevention due to their iron, vitamin, and mineral content. Continuous education is required to maintain adherence to iron supplementation and promote a balanced diet.